Unveiling the Chemistry behind the Green Synthesis of Metal Nanoparticles. Issue 9 (1st August 2014) - Santos, Sónia A. O.; Pinto, Ricardo J. B.; Rocha, Sílvia M.; Marques, Paula A. A. P.; Neto, Carlos Pascoal; Silvestre, Armando J. D.; Freire, Carmen S. R.
Abstract Nanobiotechnology has emerged as a fundamental domain in modern science, and metallic nanoparticles (NPs) are one of the largest classes of NPs studied because of their wide spectrum of possible applications in several fields. The use of plant extracts as reducing and stabilizing agents in their synthesis is an interesting and reliable alternative to conventional methodologies. However, the role of the different components of such extracts in the reduction/stabilization of metal ions has not yet been understood clearly. Here we studied the behavior of the main components of a Eucalyptus globulus Labill. bark aqueous extract during metal‐ion reduction followed by advanced chromatographic techniques, which allowed us to establish their specific role in the process. The obtained results showed that phenolic compounds, particularly galloyl derivatives, are mainly responsible for the metal‐ion reduction, whereas sugars are essentially involved in the stabilization of the NPs.